A pan-cancer analysis of MARCH8: molecular characteristics, clinical relevance, and immuno-oncology features - Zihan Quan; Songqing Fan; Hongmei Zheng; Yue Ning; Yang Yang (Cancer Biology & Therapy)
Membrane-associated RING-CH8 (MARCH8) is a member of the recently discovered MARCH family of ubiquitin ligases. MARCH8 has been shown to participate in immune responses. However, the role of MARCH8 in prognosis and immunology in human cancers remains largely unknown. The expression of MARCH8 protein was detected via immunohistochemistry in non-small cell lung cancer (NSCLC) and non-cancerous lung tissues. The study investigated the role of MARCH8 in tumor immunity through pan-cancer analysis of multiple databases. MARCH8 genetic alternations and expression were explored with the cBioPortal, GTEx, and TCGA databases. We investigated the role of MARCH8 expression in clinical relevance, prognosis, tumor immune microenvironment, immune checkpoint (ICP) with a series of bioinformatics tools and methods, such as TISIDB database, ESTIMATE, and CIBERSORT method. MARCH8 expression showed cancer-specific dysregulation and was associated with the prognosis of patients in various cancers. MARCH8 was related to the tumor microenvironment and participated in tumor immune regulation. Furthermore, low expression of MARCH8 was associated with poor prognosis and might serve as an independent prognostic biomarker for NSCLC patients. The comprehensive pan-cancer analysis revealed the potential of MARCH8 in tumor-targeted therapy, and suggested MARCH8 as a promising prognostic and immunological pan-cancer biomarker.